Hubungan Faktor Lingkungan Fisik Rumah, Keberadaan Breeding Places, Perilaku Penggunaan Insektisida dengan Kejadian DBD Di Kota Semarang - Nafifah Rahmayanti; Nur Endah Wahyuningsih; Resa Ana Dina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Currently dengue fever is still one of the public health problem on a global scale, national and regional levels. In 2014 there were 1,628 cases (IR = 92.43). Affecting factors of the incidence of dengue there are physical environmental factors, the existence of breeding places, the behavior of using of insecticides and stress levels. The purpose of this study was to analyze the relationship between the physical environment, the presence of breeding places, the behavior of using of insecticides with the incidence of dengue in the city of Semarang and to describe the espondents's stress level. This type of this research is an analytic observational with case control approach. Samples of this study are patients with DHF in March until May 2016 in Semarang. The case group were 41 respondents and the control group were 41 respondents. Data analysis using chi square test and the magnitude of the risks by using odds ratios (OR). The results showed there are no relationship between the house temperature (p = 1,000 OR = 0,488), the house humidity (p = 0.440 OR = 0.5856), the existence of breeding places (p=1,000 OR=1,000), and the behaviour of using insecticides (p = 0.258 OR = 1.860).